Bilateral giant angiomyolipomas revealed after massive retroperitoneal hemorrhage – A case report - Petrović, Sladjana; Tasić, Aleksandar; Mihailović, Dragan; Živković, Nikola; Vitanović, Marija; Stojanov, Dragan (Vojnosanitetski pregled, 2014)
Introduction. Angiomyolipomas (AML) are benign neoplasms composed of fat, smooth muscle and thick-walled blood vessels in varying proportions. These tumors have a significant female predominance. Case report. We reported a 61-year-old man with spontaneous rupture of AML. Computerized tomography revealed a change in morphology of both kidneys. Multiple lesions of fat density with dilated blood vessels were found in the left kidney. The right retroperitoneum was obliterated with a giant heterogeneous mass originating from the right kidney with a massive hemorrhage, active extravasations, compression of inferior the vena cava and intraperitoneal collections. After radical nephrectomy, histological examination revealed that the tumor was composed of relative proportions of fat, smooth muscle and blood vessels. We incidentally found small renal adenoma. Conclusion. The true nature of AML is unclear, but they are usually classified as hamartomas. Angiomyolipomas are generally benign lesions, although the epithelioid angiomyolipoma, a subtype that occurs in about 3% of cases, can behavior aggressively.